Efek Sitotoksik, Antiproliferatif dan Apoptosis Serum Tikus (Rattus novergicus Berkenhout, 1769) diberi Serbuk Tokek (Gekko gecko L.) Per Oral Terhadap Sel WiDR - Triana nuryastuti; Rarastoeti Pratiwi; Nyoman Puniawati Soesilo (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2017)
Gecko is one of the reptiles are used as traditional Chinese medicine which has been reported as antitumor capabilities. The purpose of this study was to determine the cytotoxic effect of rat serum that treated with gecko powder and its ability to inhibit proliferation and stimulate apoptosis of WiDr cells. Gecko powder the treated in vivo in the rat (Rattus novergicus) SD female. Twelve mice treated with powder gecko at a dose of 9 g/kg body weight per day. Then the rat blood serum on the in vitro treated in WiDr cells. Cytotoxicity test using the MTT method. Observation of the proliferation kinetics using doubling time test. Then apoptosis test performed by the doublestaining method. Cytotoxicity assay results showed that the powder is toxic to the gecko cell WiDr. In the cytotoxicity test showed IC50rat serum with gecko powder body parts obtained at a concentration of 7,914%. The observation of cell proliferation kinetics demonstrated rat serum with gecko powder body parts most effective in inhibiting the proliferation of WiDr cells Data apoptotic WiDr cells showed the rat serum with gecko powder effective agency in promoting apoptosis. Rat serum with treat gecko powders bodies part are toxic and can inhibit proliferation and stimulate apoptosis of WiDr cells.